Rural Destinations And Tourists' Satisfaction - Lo, May-Chiun; Peter, Songan; Abang Azlan, Mohamad; Wee, Alvin Yeo (Institute for International Management and Technology, 2011)
Past studies have shown that good service quality often leads to a better performance and higher satisfaction level. This study examines service quality dimensions and its impact on Bario, a rural tourism destination in Malaysia. Five dimensions of service quality namely, places of interest, sceneries, outdoor activities, atmosphere, and motives interest, have been chosen as the focus of this study on tourists' satisfaction. This study focuses on tourists, who visited Bario between August 2009 and January, 2010, as a population of interest. One hundred and forty six local and foreign tourists participated in this study, which attempted to add to the sparse research and to bridge the gap between service quality and tourists' satisfaction in the rural destination. The analysis has shown that different service quality components had various impacts on tourists' satisfaction. The results of this study propose that places, outdoor and atmosphere are the important dimensions to enhance tourists' satisfaction. Implications of the findings, potential limitations of the study, and directions for future research, are discussed.